State Dependency to Optimize Access of Home Appliances using Remote Control - Vijaya Sri Kompalli, Dr; Sandhya, K; Asritha Thanmai, K; Siva Sree, D (International Journal of Engineering and Technology, 2018)
Internet of Things (IoT) is a combination of hardware and software technology that produces trillions of data by connecting multiple devices and sensors with the cloud and computing and accessing the required data through intelligent means of connecting and utilizing various tools. With numerous connected devices and appliances, the smart home is one of the emphasized areas of IoT. Smart home concept deals with inter connecting the working of multiple devices using IoT. In view of this, multiple home appliances are operated using the common remote controller access. When IoT devices are meant to operate based on remote control there is an immense role of identifying the state dependencies of various devices. If one device is in ON state, then it will show the status of other devices also whether to be in ON state or OFF state or choice of none of devices to be in state of ON or OFF. Till now, state dependencies of devices in home appliances are manually identified. Therefore, in order to control devices of home appliances with in a precise location, a design issue based on identification of state dependencies by using graph matrices for multiple devices can be made for better utilization to save energy and also to restrict the unnecessary access of devices.Â Â